PENINGKATAN KEMAMPUAN BERBICARA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE BERCERITA BERPASANGAN PADA SISWA KELAS V SDN 23 SEMBAWA KABUPATEN BANYUASIN - Monalisa Monalisa; Missriani Missriani; Siti Rukiyah (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to improve the speaking skills of fifth-grade students at SDN 23 Sembawa, Banyuasin Regency, through the implementation of the paired storytelling cooperative learning model. The research used Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 20 students. Data were collected through speaking skill tests, observations of teacher and student activities, and documentation. The results showed an improvement in students’ speaking skills from the pre-action stage to Cycle I and a more significant increase in Cycle II. The improvement was seen in pronunciation, intonation, diction, fluency, topic mastery, expression, and students’ confidence in speaking. Classical learning mastery achieved the success criteria, with at least 85% of students obtaining scores of 70 or higher. The paired storytelling cooperative learning model also enhanced students’ activeness, cooperation, and self-confidence during the learning process. Therefore, this model is effective in improving elementary students’ speaking skills.